THE APPLICATION OF RANGE OF VARIABILITY APPROACH TO THE ASSESSMENT OF A CHECK DAM ON RIVERINE HABITAT ALTERATION - Shieh Ch.; Guh Yu.; Wang Sh. (My University, 2007)
This report uses the intermediate disturbance hypothesis to assess the influence of constructing a check dam on river environment. HEC-HMS and HEC-RAS programs were used to generate hydraulic parameters such as flow discharge, water depth, velocity, water surface width and sediment discharge. Indicators of hydrologic alteration (IHA) and indicator of habitat alteration (IHabA) were used to evaluate the flow and habitat conditions before and after check dam construction. The range of variability approach was used to calculate the degree of hydrologic alteration for each IHA, degree of habitat alteration and overall alteration for IHabA. Variability of river habitats before and after check dam construction was contrasted. Alteration became larger the closer to the dam body. An assessment method for check dam construction is offered which does not require ecological investigation data and combines ecology concepts and hydraulics.
Keywords: AQUATIC ECOSYSTEMS; RANGE OF VARIABILITY APPROACH; HABITAT ALTERATION; STREAM SEDIMENTATION; CHECK DAM; INTERMEDIATE DISTURBANCE HYPOTHESIS; TAIWAN